The Role of Bilingual Flash Card Learning Media in Improving Students' Understanding in Elementary Schools - Ningsih, Ayu Fitria; Saputri, Farica Dwi; Hariyani, Oktavia Lisa; Safitri, Henis Wahyu; Widagdo, Arif (EDUCTUM: Journal Research, 2025)
The purpose of this study is to investigate how bilingual flashcards can be used as a teaching tool to help elementary school students understand concepts better. The research approach is a comprehensive literature evaluation that looks at related books, research papers, and scientific publications. The results show that bilingual flashcards help students become more proficient in language, especially in vocabulary acquisition, pronunciation, and content retention. Visual and interactive flashcards can increase student motivation and encourage active participation in the learning process. Many studies show that this medium can be used to improve Indonesian language learning, especially in identifying standard and non-standard vocabulary. This medium is also useful for learning other languages. Additionally, this medium is cost-effective, flexible, and easy to implement in small classrooms. However, its utilization remains uneven due to limitations in teachers' understanding and skills in designing and using the medium optimally. Therefore, teacher training and guidance are needed to maximize the use of bilingual flashcards in supporting language learning success at the elementary school level.